Development of functionalized quantum dot modified poly(vinyl alcohol) membranes for fuel cell applications. Issue 53 (16th May 2016) - Malik, Rajender Singh; Soni, Udit; Singh Chauhan, Sampat; Verma, Pawan; Choudhary, Veena
Abstract : Superior thermally, hydrolytically and mechanically stable heat treated functionalized quantum dot modified PVA membranes with enhanced proton conductivity are reported. Abstract : This paper describes the preparation and characterization of membranes based on poly(vinyl alcohol) (PVA) cross-linked using functionalized CdSe quantum dots [FQDs] (size 4 ± 0.2 nm). FQDs having –COOH and –SO3 H functionalities on the surface were synthesized by the ligand exchange method using a mixture of 3-mercaptopropionic acid and 2-mercaptoethanesulfonic acid. Both sulfonic (–SO3 H) and carboxylic (–COOH) groups are expected to enhance the dimensional/thermal stability of PVA [by cross-linking] and proton conductivity [as proton donors]. Several membranes were prepared by mixing an aqueous solution of PVA with varying amounts of FQDs and then cross-linked by thermal treatment. Cross-linked membranes were characterized for structural (FTIR-ATR) and thermal behaviour (TGA, DSC, DMA), morphology (SEM, TEM, XRD), water uptake and proton conductivity. Hydrolytic stability and T g increased with increasing degree of cross-linking. All of the cross-linked membranes had proton conductivity of 10 −3 S cm −1 in the temperature range of 25 °C to 70 °C at 100% relative humidity.